2018
DOI: 10.1016/j.yjmcc.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Beta1-adrenoceptor antagonist, metoprolol attenuates cardiac myocyte Ca2+ handling dysfunction in rats with pulmonary artery hypertension

Abstract: Right heart failure is the major cause of death in Pulmonary Artery Hypertension (PAH) patients but is not a current, specific therapeutic target. Pre-clinical studies have shown that adrenoceptor blockade can improve cardiac function but the mechanisms of action within right ventricular (RV) myocytes are unknown. We tested whether the β1–adrenoceptor blocker metoprolol could improve RV myocyte function in an animal model of PAH, by attenuating adverse excitation-contraction coupling remodeling. PAH with RV fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 45 publications
6
37
0
Order By: Relevance
“…Despite this, observational trials of PH patients who receive β-AR blockers for co-morbidity reasons demonstrated the safety of the drugs in this cohort [16, 17]. Promising preclinical experimental evidence for β-AR blocker treatment for right heart failure in rat models of PH is now emerging [1822].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, observational trials of PH patients who receive β-AR blockers for co-morbidity reasons demonstrated the safety of the drugs in this cohort [16, 17]. Promising preclinical experimental evidence for β-AR blocker treatment for right heart failure in rat models of PH is now emerging [1822].…”
Section: Introductionmentioning
confidence: 99%
“…Metoprolol is a selective β1-adrenoceptor inhibitor, that has been widely used to improve heart function [36,37]. Many studies have shown that long-term treatment with Met could downregulate collagen I and III mRNA levels, and modulate stem cell characteristics to prevent progressive pathological remodeling, in addition, Met could improve the Ca 2+ handling and contractility of right ventricular (RV) myocytes isolated from monocrotaline (MCT)-treated rats [18,[38][39][40]. In embryonic development, β-adrenoceptor stimulation leads to decreased AKT phosphorylation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Metoprolol (Met) is a β-blocker widely used to inhibit cardiac hypertrophy and to improve cardiac function [18,19]. Nebivolol, which is a third-generation β-blocker, has antihypertrophic effects in models of neonatal cardiomyocyte hypertrophy [20].…”
mentioning
confidence: 99%
“…Calcium influx is also considered to account for many detrimental effects of traditional inotropic drugs, such as glycosides digoxin [ 26 ]. Imbalance of calcium homeostasis in the cardiomyocytes not only directly interferes myocardial contraction and relaxation through calcium/calmodulin-dependent proteins but also exacerbates the heart failure process by interacting with other pathophysiological factors such as the β -adrenergic signaling pathway and renin-angiotensin-aldosterone system (RAAS) [ 27 30 ]. These pathophysiological changes were also confirmed by our experimental results.…”
Section: Discussionmentioning
confidence: 99%